The umbilical cord, preeclampsia and the VEGF family - Olaya-C M; Garrido M; Hernandez-Losa J; Sesé M; Ayala-Ramirez P; Somoza R; Vargas MJ; Ramón y Cajal S (Dove Medical Press, 2018)
Mercedes Olaya-C,1 Marta Garrido,2 Javier Hernandez-Losa,2–4 Marta Sesé,2–4 Paola Ayala-Ramirez,5 Rosa Somoza,2–4 Magda Jimena Vargas,6 Santiago Ramón y Cajal2–4 1Department of Pathology, Institute of Human Genetics, The Medical School, Pontificia Universidad Javeriana - Hospital Universitario San Ignacio, Bogota, Colombia; 2Pathology Department, Vall d’Hebron Hospital, Barcelona, Spain; 3Translational Molecular Pathology, Vall d’Hebron Research Institute (VHIR), Universitat Autònoma de Barcelona, Barcelona, Spain; 4Spanish Biomedical Research Network Center in Oncology (CIBERONC), Barcelona, Spain; 5Institute of Human Genetics, The Medical School, Pontificia Universidad Javeriana, Bogota, Colombia; 6Department of Pathology, The Medical School, Pontificia Universidad Javeriana - Hospital Universitario San Ignacio, Bogota, Colombia Introduction: The VEGF family has been identified as abnormal in preeclampsia (PE). Hypertensive disorders of pregnancy (HDP) are major contributors to maternal and neonatal morbidity and mortality worldwide; likewise, umbilical cord anatomical abnormalities (UCAA) are linked to poor neonatal outcomes. Based on the relationship described between PE and UCAA and the role of the VEGF family in PE, this study explored VEGF expression in placental and UC tissued from patients with PE and with UCAA.Methods: We performed an observational, analytical study on placentas, comparing protein and mRNA expression in four groups: patients with PE, patients with UC abnormalities, patients with both, and patients with none of them. Using immunohistochemistry, we studied VEGF A, VEGF R1 (FLT1), MMP1, and PLGF. With quantitative reverse transcription polymerase chain reaction we described mRNA expression of PLGF, VEGF and sFLT1, and sFLT1/PLGF ratio.Results: Forty newborns were included. Sixty-seven percent of mothers and 45% of newborns developed no complications. Immunohistochemistry was performed on UC and placental disc paraffin-embedded tissue; in the latter, the mRNA of the VEGF family was also measured. Statistically significant differences were observed among different expressions in both HDP and UCAA groups. Interestingly, the UCAA group exhibited lower levels of sFLT1 and VEGF-A in comparison with other groups, with significant P-value for sFLT1 (P=0000.1).Conclusion: The origin of UCAA abnormalities and their relation with HDP are still unknown. VEGF family alterations could be involved in both. This study provides the first approach related to molecules linked to UCAA. Keywords: preeclampsia, umbilical cord, VEGF, sFLT1, PLGF, stillbirth